(untitled) (Journal of Engineering, 2009)
Scrap metal export is currently one of the few thriving industries in Iraq. Looters and legitimate operators are together effectively demolishing many of the old industrial facilities in order to retrieve the metal contained in buildings, processes and storage equipments and vehicles. The mixing of civilian and military scrapping operations such as that occurring at Ouireej is exacerbating the problem. The situation is particularly difficult for Iraq, given the rapid growth of the scrap industry and the lack of security. In view of the current difficulties, the focus was on practical short to medium term improvements such as controlling access to sites, land use zoning, licensing and export controls. The wholesale reform of the scrap metal industry to improve environmental practices, whilst desirable, is also probably not feasible in the short to medium term. The remediation of working scrap sites, such as Ouireej is also probably unfeasible at present. Laboratory analysis of shallowsoil detected contamination by PCBs, mineral oil and heavy metals, principally copper, lead, antimony and Zinc. The detected levels of all contaminants were relatively low. But PCB contamination was relatively widespread, being detected in eight soil samples with a maximum concentration of 23 μg/kg. Laboratory analysis of rainwater ponds on the site indicated marginal contamination by heavy metals and mineral oils